An individual approach to monitoring locomotive training load in English Premier League academy soccer players - Abbott, W.; Brickley, G.; Smeeton, N. J. (International Journal of Sports Science & Coaching, 2018)
To account for the individual intensity of locomotion tasks, individualised speed thresholds have been proposed as an alternative to global speed thresholds. Methodologies to determine individual speed thresholds have typically been laboratory based, time consuming and expensive, rendering them inappropriate for applied practitioners working with large squads. The current investigation utilised easy-to-administer field tests to individualise speed thresholds. The aim was to investigate differences between high-speed locomotion measured using global and individual speed thresholds. Nineteen, male, professional soccer players completed maximum sprint and maximum aerobic speed protocols and were divided into groups dependent upon maximum aerobic speed performance (high, medium and low). Locomotion data were collected using portable Global Positioning System units and analysed using global and individual analysis methods to determine distances travelled performing high-speed running, very high-speed running and sprinting. In low athletes, the individual analysis method produced significantly higher percentages of high-speed running, very high-speed running and sprinting compared to global (mean differences 7.8%, 6.1% and 1.7%, respectively, all p<0.001). In medium athletes, no significant differences were found between analysis methods for high-speed running and very high-speed running. In high athletes, the individual analysis method produced significantly lower high-speed running and very high-speed running percentages compared to global (mean differences 11.0% and 6.8%, p<0.001). Results concluded that global thresholds produced high-speed locomotion percentages significantly higher or lower than individual thresholds for 47% of athletes. The current investigation recommends the use of field tests to individualise speed thresholds, allowing applied practitioners to accurately quantify individual athlete intensity.